Teaching at the Right Level Approach in Problem-Based Learning Design - Leasa, Marleny; Tuhurima, David; Laurens, Theresia (Unram Journal of Community Service, 2024)
Community Service (known with PkM) activities were carried out by providing training to teachers in North West Seram District, Central Maluku Regency. This activity aims to provide insight into the development of teacher professionalism, more specifically how deep the application of Teaching at the Right Level (TaRL) in learning activities in schools. The activity was carried out through direct face-to-face meetings with teachers. The results of this service are known that teachers gain a lot of knowledge about strategies for connecting learning with a cultural background and referring to the level of student ability. In addition, more than 100 teachers were satisfied with the activities carried out, which were based on the level of student knowledge with the TaRL approach using the problem-based learning model. The teachers hope that the PkM Team can continue to provide assistance so that the implementation of learning activities in the classroom can run well. This is because TaRL is a new method for teachers in remote areas so that it requires adjustments in implementation in learning